Analysis of pyrrolizidine alkaloids in stingless bee honey and identification of a botanical source as Ageratum conyzoides - Hungerford, Natasha L.; Zawawi, Norhasnida; Zhu, Tianqi; Carter, Steve J.; Melksham, Kevin J.; Fletcher, Mary T. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Stingless bee honeys (SBHs) from Australian and Malaysian species were analysed using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) for the presence of pyrrolizidine alkaloids (PAs) and the corresponding N-oxides (PANOs) due to the potential for such hepatotoxic alkaloids to contaminate honey as a result of bees foraging on plants containing these alkaloids. Low levels of alkaloids were found in these SBHs when assessed against certified PA standards in targeted analysis. However, certain isomers were identified using untargeted analysis in a subset of honeys of Heterotrigona itama which resulted in the identification of a PA weed species (Ageratum conyzoides) near the hives. The evaluation of this weed provided a PA profile matching that of the SBH of H. itama produced nearby, and included supinine, supinine N-oxide (or isomers) and acetylated derivatives. These PAs lacking a hydroxyl group at C7 are thought to be less hepatoxic. However, high levels were also observed in SBH (and in A. conyzoides) of a potentially more toxic diester PA corresponding to an echimidine isomer. Intermedine, the C7 hydroxy equivalent of supinine, was also observed. Species differences in nectar collection were evident as the same alkaloids were not identified in SBH of G. thoracica from the same location. This study highlights that not all PAs and PANOs are identified using available standards in targeted analyses and confirms the need for producers of all types of honey to be aware of nearby potential PA sources, particularly weeds.